2003
DOI: 10.1038/sj.onc.1206975
|View full text |Cite
|
Sign up to set email alerts
|

Transient expression of E1A and Ras oncogenes causes downregulation of c-fos gene transcription in nontransformed REF52 cells

Abstract: Stable transformation of rat embryo fibroblast (REF) cells with E1A and cHa-ras oncogenes leads to downmodulation of c-fos gene transcription. This repression is provided in part by the association of Elk-1 transcription factor with histone deacetylases mediated through effects of Ras on MAP-kinase cascades. Here, we focus on the primary effects of E1A and Ras displayed in transient transfection assay on the transactivating capability of Elk-1, which is a key transcription factor of c-fos gene regulation. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The question why this phenomenon is only observed after extinction needs further investigation. Our hypothesis that ERK may form complexes with HDAC1 or mSin3A, which are known to repress c-Fos (Usenko et al, 2003; Yang et al, 2001) was not confirmed. The possibility remains that pERK targets JunD and JDP2 to AP-1 and subsequently dephosphorylates and dissociates from them.…”
Section: Discussionmentioning
confidence: 71%
“…The question why this phenomenon is only observed after extinction needs further investigation. Our hypothesis that ERK may form complexes with HDAC1 or mSin3A, which are known to repress c-Fos (Usenko et al, 2003; Yang et al, 2001) was not confirmed. The possibility remains that pERK targets JunD and JDP2 to AP-1 and subsequently dephosphorylates and dissociates from them.…”
Section: Discussionmentioning
confidence: 71%
“…HDAC1 activity has been implicated in the regulation of the expression of c-Fos (Yang et al, 2001;Usenko et al, 2003;Renthal et al, 2008), an immediate early gene that is transiently upregulated after contextual fear conditioning (Radulovic et al, 1998;Peleg et al, 2010) and whose protein levels are reduced after extinction training (Tronson et F ϭ 12,78). B, Top, Experimental design.…”
Section: Hdac1-mediated Transcriptional Repression During Fear Extincmentioning
confidence: 99%
“…Many of the pathways in the merged networks shown in Figure 7c converge on FOS, one of the downstream effectors of the MAPK/Erk signalling cascade involved in growth and differentiation, which the comparative analysis suggests is significantly dysregulated in the Ad5 E1-TC (Figure 4 ). Expression of c-fos is suppressed in some human tumours [ 27 ] and also in rat embryo fibroblast cells transiently transfected or stably transformed by Ad E1A and Ras, acting on chromatin remodelling factors [ 28 ]. The extracellular signal-regulated kinase (ERK) pathway is one of three major mammalian mitogen-activated protein kinase (MAPK) signalling pathways; the others being the p38 MAPK pathway, and the c-Jun NH 2 -terminal kinase (JNK) pathway.…”
Section: Resultsmentioning
confidence: 99%